Peningkatan Prestasi Belajar Siswa dengan Model Pembelajaran Kooperatif Make A Match pada Mata Pelajaran IPS di Kelas IV SD Inpres Borong Jambu I Kecamatan Manggala Kota Makassar - R Supardi; Waddi Fatimah; Perawati Bte Abustang (STKIP Andi Matappa Pangkep, 2021)
This study aims to increase student achievement with the Make A Match Cooperative Learning Model in Social Studies Subjects in Class IV SD Inpres Borong Jambu I, Manggala District, Makassar City. This type of research is classroom action research. The subjects of this study were students IV of SD Inpres Borong Jambu I, totaling 20 students, consisting of 11 male students and 9 female students. This research was conducted in two cycles of action. Each cycle contains planning, implementation, observation and reflection activities. The research instrument used is observation, test and documentation. Based on the results of the study showed that student learning outcomes experienced a significant increase in each cycle which was marked enough, the first cycle with an average value of 65.6 then increased in the second cycle with an average value of 77.3 to achieve good criteria. Based on the results obtained, it was concluded that there was a significant increase in social studies learning outcomes for fourth grade students of SD Inpres Borong Jambu I, Manggala District, Makassar City through the Make A Match Cooperative learning model.